2022
DOI: 10.3390/molecules27041452
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Autoantibody Signatures in Rheumatoid Arthritis

Abstract: For the identification of antigenic protein biomarkers for rheumatoid arthritis (RA), we conducted IgG profiling on high density protein microarrays. Plasma IgG of 96 human samples (healthy controls, osteoarthritis, seropositive and seronegative RA, n = 24 each) and time-series plasma of a pristane-induced arthritis (PIA) rat model (n = 24 total) were probed on AIT’s 16k protein microarray. To investigate the analogy of underlying disease pathways, differential reactivity analysis was conducted. A total of n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…The top 10 differentially reactive proteins, based on the mean change in reactivity between classes of these antigens, are summarized in the Table 1 glioblastoma contrasts (a,c,e) and in the Table 1 meningioma contrasts (c,d,f). The p -values and fold changes derived from the protein array analysis were in a moderate range, which was consistent with our previous studies performed on other cancers, and also on inflammatory (ulcerative colitis) and autoimmune (rheumatoid arthritis) diseases [ 9 , 10 ]. The diagnostic potential of serotesting showed the potential of the candidate biomarkers based on the AUC values, although the sample numbers were low, and need to be confirmed in larger studies.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The top 10 differentially reactive proteins, based on the mean change in reactivity between classes of these antigens, are summarized in the Table 1 glioblastoma contrasts (a,c,e) and in the Table 1 meningioma contrasts (c,d,f). The p -values and fold changes derived from the protein array analysis were in a moderate range, which was consistent with our previous studies performed on other cancers, and also on inflammatory (ulcerative colitis) and autoimmune (rheumatoid arthritis) diseases [ 9 , 10 ]. The diagnostic potential of serotesting showed the potential of the candidate biomarkers based on the AUC values, although the sample numbers were low, and need to be confirmed in larger studies.…”
Section: Resultssupporting
confidence: 90%
“…These antibody profiles are an additional layer of omics, that can also be called the immunome , due to their broad spectrum of reactive binding of antibodies, elucidated in parallel on protein arrays. In previous work, we have shown that the immunome provides biologically meaningful information in cancer [ 6 , 7 , 8 ] and autoimmune diseases (rheumatoid arthritis) [ 9 ], and in inflammatory diseases (ulcerative colitis, [ 10 ]). Regarding the current trend in immuno-oncology, antigenic reactivity has aroused great interest, and several therapeutic approaches are being considered and studied, to improve glioblastoma treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, also autoantibodies to native proteins may be detectable in sera of RA patients including also a subset of seronegative patients. In recent years several array-based studies have revealed novel candidate antigens for seronegative disease including peptides derived from joint specific antigens RA [55][56][57][58]. Although some candidates seem promising, confirmation in larger multicenter cohorts is required to confirm their potential value for RA diagnostics.…”
Section: Seronegative Ra -Beyond Rheumatoid Factors and Antimodified ...mentioning
confidence: 99%
“…In this study, we analyzed the immunological responses of patients with SJIA, using human proteome arrays presenting immobilized recombinantly expressed human proteins. These arrays have been previously used in studies analyzing antibody profiles in cancer patients and patients with rheumatic arthritis and ulcerative colitis [ 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%